Review on Business Intelligence Tools - Kejriwal, Mudit (International Journal of Psychosocial Rehabilitation, 2020)
The augmenting number of SMEs (small and medium-sized enterprises) has resulted in a multitude of naive businessmen. Adding to that, there is a lack of realization of the scale to which their business data can help them grow. Consequently, the SMEs store data in an unstructured and unorganized fashion, which can hardly be employed for business analytics and discovering trends and frequent patterns. The goal is to have an interface to get feed the data in a structured manner so as to track down trends and other overlooked aspects of an enterprise such as return on capital, KPIs (key performance indicators), break-even point etc. to suggest business actions to those SMEs to increase their profits and thereby helping them grow their business. The BI (business intelligence) tools currently in the market are targeted for large enterprises and require a significant amount of investments on infrastructure. Moreover, the current tools are cumbersome for the SMEs to install and operate. Any SME needs nothing more than a simple ETL (extract-transform-load) implementation along with supporting dashboards and analytics to make the BI tool easy to use and on-the-go. This paper is a brief study of the existing approaches to business intelligence implementation. This paper will help understand the compatibility of these approaches for any small or medium enterprise.